Endapan Teras Sebagai Kendali Profil Saprolit Kasus Zone Transisi Formasi Sambipitu-Oyo di Sungai Widoro Km.28,10 Yogyakarta-Wonosari - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Studi S1 Gizi Kesehatan Fak. Kedokteran UGM, 2006)
River Widoro at UTM coordinate 04500601912798Z as a location of transition zone Sambipitu-Oyo Formation, consist of sandy limestone, covered by terrace deposits. Profile research of sandy limestone saprolite based on outcrop and thin section. Bed rock is sandy allochem limestone (Hu-1), has a lamination structure, experience corrosion and oxidation. The lower saprolite horizon is muddy allochem limestone (Hu-2), fractured with sharp boundary, develop tepee and relict of lamination structure. Continously water reaction from terrace deposits to rock produce mineral addition, dissolved and chemical weathering. Allochemic mudstone (Hu-3) is the upper saprolite horizon with relict texture of bed rock. Ore mineral, clay, and ferro oxide in Hu-3 are increase, sparite dissolved. Structural and textural changes as a result of water volume and turbidity are still strong.